Tourism Opportunities in Jammu and Kashmir and Fresh Terror Attacks - Sharma, S. K (Journal of Commerce and Trade, 2021)
Tourism is a large and growing part of the economy of many countries of the world. India is a country known for its lavish treatment to all visitors, no matter where they come from. Its visitor-friendly traditions, varied life styles and cultural heritage and colorful fairs and festivals held abiding attractions for the tourists. Beautiful sites and landscapes, forests and wild life, adventurous mountains, pilgrimage and medical treatment are some attractions for foreign and domestic population. Kashmir as a tourist destination has incomparable beauty and it is known as "Paradise on Earth". Kashmir is also known for its unique cultural ethos which has evolved through centuries in a seamless co-existence called Kashmiriyat, a second name for hospitality. Two major Himalayan ranges, the greater Himalayas and the Pir Panjal, surrounds the valley from the north and the South respectively. But unfortunately, the outbreak of terrorist incidents from 1989 toppled tourist inflow towards valley, which left its deep mark on the economy of the concerned territory. Classification-JEL : K42, Z31, Z32